Feasibility of exercise stress echocardiography for cardiac risk assessment in chronic kidney disease patients prior to renal transplantation. Issue 10 (9th August 2016) - Nerlekar, Nitesh; Mulley, William; Rehmani, Hassan; Ramkumar, Satish; Cheng, Kevin; Vasanthakumar, Sheran A.; Rashid, Hashrul; Barton, Timothy; Nasis, Arthur; Meredith, Ian T.; Moir, Stuart; Mottram, Philip M.
Abstract: Background: Pharmacologic stress testing is utilized in preference to exercise stress echocardiography (ESE) for cardiac risk evaluation in potential renal transplant recipients due to the perceived lower feasibility of ESE for achieving adequate workload and target heart rate (THR) in this population. Methods: Consecutive patients referred for cardiac risk evaluation prior to potential kidney transplantation were evaluated. All patients attempted ESE before pharmacologic testing was considered. Treadmill ESE utilized BRUCE protocol to maximum capacity. THR was defined as >85% of the maximum predicted heart rate (220‐age). Functional capacity was assessed by metabolic equivalents (METs) and the rate pressure product (RPP). Results: Of 535 patients (349 male, age 56±11), 372(70%) reached THR. Mean METs were 10±3 with 531(99%) achieving ≥4 METs and 87% ≥7 METs. Mean RPP was 25 821±5820 bpm×mm Hg (83% achieving >20 000 bpm×mm Hg). On multivariate analysis, independent predictors of failure to reach THR were rate‐control medication and diabetes; failure to reach 7 METs: females, diabetics, age≥65, and previous cardiac disease; failure to reach RPP>20 000: rate‐control medication. There were 97% of ESE completed to physiologic endpoints. Conclusion: In unselected potential renal transplant candidates, cardiac assessment by ESE is well tolerated, with 9‐in‐10 exercising to satisfactory functional capacity. ESE should be considered a feasible alternative to pharmacologic testing in this population.